Multipliers in Holomorphic Mean Lipschitz Spaces on the Unit Ball. (18th June 2012) - Cho, Hong Rae
Abstract : For1 ≤ p ≤ ∞ ands > 0, letΛ s p be holomorphic mean Lipschitz spaces on the unit ball inℂ n . It is shown that, ifs > n / p, the spaceΛ s p is a multiplicative algebra. Ifs > n / p, then the spaceΛ s p is not a multiplicative algebra. We give some sufficient conditions for a holomorphic function to be a pointwise multiplier ofΛ n / p p .